A chromatographic method for the production of a human immunoglobulin G solution for intravenous use - K. Tanaka; E. Sawatani; E.M. Shigueoka; T.C.X.B. Campos; H.C. Nakao; G.A. Dias; R.K. Fujita; F. Arashiro (Brazilian Journal of Medical and Biological Research, 1998)
Immunoglobulin G (IgG) of excellent quality for intravenous use was obtained from the cryosupernatant of human plasma by a chromatographic method based on a mixture of ion-exchange, DEAE-Sepharose FF and arginine Sepharose 4B affinity chromatography and a final purification step by Sephacryl S-300 HR gel filtration. The yield of 10 experimental batches produced was 3.5 g IgG per liter of plasma. A solvent/detergent combination of 1% Tri (n-butyl) phosphate and 1% Triton X-100 was used to inactivate lipid-coated viruses. Analysis of the final product (5% liquid IgG) based on the mean for 10 batches showed 94% monomers, 5.5% dimers and 0.5% polymers and aggregates. Anticomplementary activity was 0.3 CH50/mg IgG and prekallikrein activator levels were less than 5 IU/ml. Stability at 37ºC for 30 days in the liquid state was satisfactory. IgG was stored in flasks (2.5 g/flask) at 4 to 8ºC. All the characteristics of the product were consistent with the requirements of the 1997 Pharmacopée Européenne.